Knowledge, Attitudes, and Behaviors of Parents towards Recommended Adult Vaccinations: An Explanatory Survey in the Geographic Area of Naples, Italy - Francesco Napolitano (International Journal of Environmental Research and Public Health, 2019)
The purposes of this study were to explore the knowledge, attitudes, and behaviors towards the recommended vaccinations for adults between 19−64 years of age and the associated factors among parents. The survey was conducted from October to December 2018 among a sample of parents randomly selected from five preschools and primary, secondary, and high schools in the geographic area of Naples, Italy. The mean age of participants was 45.2 years (range 19−71). Only 16% of the parents knew all vaccinations recommended to adults between 19−64 years of age. Those being healthcare professionals, having a chronic condition, having received information about vaccinations from physicians, and having a lower educational level were more likely to know the vaccinations recommended to adults between 19−64 years of age. Female participants, those who had received information about vaccinations from physicians, and those who had a lower number of children were more likely to have a positive attitude toward the usefulness of the administration of vaccinations recommended to adults between 19−64 years of age. Among unvaccinated respondents, more than half reported a positive attitude toward willingness to receive a recommended vaccination. This positive attitude was significantly higher among those who considered vaccinations as being useful and among who had received information from physicians. Only 16.9% self-reported to have received at least one vaccination recommended to adults between 19−64 years of age. Those who were healthcare professionals, who had at least one chronic condition, and who considered the administration of the vaccinations as being useful were more likely to have received at least one recommended vaccination. Greater efforts by policy makers and healthcare providers are needed to increase parents’ knowledge on recommended vaccines, and it is also crucial that healthcare providers have a high knowledge and favorable attitudes in order to increase vaccine coverage.